Induction chemotherapy vs post-operative adjuvant therapy for malignant pleural mesothelioma. (3rd August 2017) - Marulli, Giuseppe; Faccioli, Eleonora; Bellini, Alice; Mammana, Marco; Rea, Federico
ABSTRACT: Introduction : Malignant pleural mesothelioma (MPM) is an aggressive neoplasia. Multidisciplinary treatments, including the association of induction and/or adjuvant therapeutic regimens with surgery, have been reported to give encouraging results. Current therapeutic options are not well standardized yet, especially regarding the best association between surgery and medical treatments. The present review aims to assess safety, efficacy and outcomes of different therapies for MPM. Areas covered : This article focuses on the multimodality treatment of mesothelioma. A systematic review was performed by using electronic databases to identify studies that considered induction and adjuvant approaches in MPM therapy in a multidisciplinary setting, including surgery. Endpoints included overall survival, disease free survival, disease recurrence, and complications. Expert commentary : This systematic review offers a comprehensive view of current multidisciplinary therapeutic strategies for MPM, suggesting that multimodality therapy offers acceptable outcomes with better results reported for trimodality approaches. Individualization of care for each patient is fundamental in choosing the most appropriate treatment. The growing complexity of treatment protocols mandates that MPM patients be referred to specialized Centers, in which every component of the interdisciplinary team can provide the necessary expertise and quality of care.